Róbert Kiss Szemán: "…Garázda emberek az Etymologusok". Irodalmi tanulmányok: Budapest: ELTE BTK, Szláv Filólogiai Tanszék, 2008, 171 pp. - Janiec-Nyitrai, Agnieszka (Slavia Centralis, 2020)
In this article, the author presented and evaluated the book by Róbert Kiss Szemán, a Hungarian writer, essayist and translator of Czech and Slovak literature into Hungarian.
Keywords: Garázda emberek az etymologusok; Róbert Kiss Szemán; literature; review; book